Dissecting the roles of Cse1 and Nup2 in classical NLS‐cargo release in vivo. (15th September 2020) - Lange, Allison; Fasken, Milo B.; Stewart, Murray; Corbett, Anita H.
Abstract: The importin α/β transport machinery mediates the nuclear import of cargo proteins that bear a classical nuclear localization sequence (cNLS). These cargo proteins are linked to the major nuclear protein import factor, importin‐β, by the importin‐α adapter, after which cargo/carrier complexes enter the nucleus through nuclear pores. In the nucleus, cargo is released by the action of RanGTP and the nuclear pore protein Nup2, after which the importins are recycled to the cytoplasm for further transport cycles. The nuclear export of importin‐α is mediated by Cse1/CAS. Here, we exploit structures of functionally important complexes to identify residues that are critical for these interactions and provide insight into how cycles of protein import and recycling of importin‐α occur in vivo using a Saccharomyces cerevisiae model. We examine how these molecular interactions impact protein localization, cargo import, function and complex formation. We show that reversing the charge of key residues in importin‐α (Arg44) or Cse1 (Asp220) results in loss of function of the respective proteins and impairs complex formation both in vitro and in vivo. To extend these results, we show that basic residues in the Nup2 N‐terminus are required for both Nup2 interaction with importin‐α and Nup2 function. These results provide a more comprehensive mechanistic model of how Cse1, RanGTP and Nup2 function in concert to mediate cNLS‐cargo release in the nucleus. Abstract : Directional transport of cargoes between the nucleus and cytoplasm is mediated by receptors that bind cargo in one compartment and release cargo into a destination compartment. Cargoes that contain a cNLS are recognized by importin‐α in the cytoplasm. Release factors including the importin‐α export receptor, Cse1, and a nuclear pore complex protein, Nup2, ensure efficient cargo delivery into the nucleus. Interactions defined by previous structural studies are required for productive interactions between importin‐α, Cse1, and Nup2 to occur in vivo.